2003
DOI: 10.3928/1081-597x-20030701-07
|View full text |Cite
|
Sign up to set email alerts
|

Laser in situ Keratomileusis for Correction of Induced Astigmatism From Cataract Surgery

Abstract: PURPOSE: To evaluate the efficacy, predictability, stability, and safety of laser in situ keratomileusis (LASIK) to correct residual astigmatism after cataract surgery. METHODS: LASIK was performed on 20 eyes of 20 patients with refractive myopic or mixed astigmatism (3.00 to 6.00 D) at least 1 year after extracapsular cataract extraction with posterior chamber intraocular lens implantation without complication. Each eye received bitoric LASIK with the Nidek EC-5000 excimer laser and the Automated Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Understanding the distribution of astigmatism is important to help ophthalmologists choose first-line treatment that will be most effective and reduce the occurrence of postoperative astigmatism. This includes procedures such as limbal relaxing incisions [11], opposite clear corneal incisions [18], excimer laser refractive procedures [9,13,14], femtosecond laser-assisted astigmatic keratotomy [15], and toric IOL implantation [16][17]. At present, toric IOL implantation is highly recognized and it can be used to correct up to 8.0 D of corneal astigmatism after cataract surgery [18,19].…”
Section: Discussionmentioning
confidence: 99%
“…Understanding the distribution of astigmatism is important to help ophthalmologists choose first-line treatment that will be most effective and reduce the occurrence of postoperative astigmatism. This includes procedures such as limbal relaxing incisions [11], opposite clear corneal incisions [18], excimer laser refractive procedures [9,13,14], femtosecond laser-assisted astigmatic keratotomy [15], and toric IOL implantation [16][17]. At present, toric IOL implantation is highly recognized and it can be used to correct up to 8.0 D of corneal astigmatism after cataract surgery [18,19].…”
Section: Discussionmentioning
confidence: 99%
“…Surface ablation procedures, such as laser-assisted in situ keratomileusis (LASIK), can be utilized to manage postoperative residual astigmatism. Norouzi et al [ 63 ] found that LASIK was effective, predictable, and safe in correcting astigmatism ranging from 3 to 6D when performed one year after routine cataract surgery.…”
Section: Postoperative Residual Astigmatismmentioning
confidence: 99%
“…[1][2][3] Toric intraocular lenses (IOLs) have been shown to be superior over LRIs or excimer laser surgery for refractive accuracy and stability while treating preexisting corneal astigmatism along with surgical aphakia. [4][5][6][7][8][9][10][11][12] One of the challenges after toric IOL implantation, however, is a potential risk of postoperative rotation and deviation from the intended axis, requiring a surgical repositioning. Rotation of a toric IOL from its intended axis can degrade its cylindrical corrective power by 3.3% for every 1 degree off axis.…”
mentioning
confidence: 99%
“…1–3 Toric intraocular lenses (IOLs) have been shown to be superior over LRIs or excimer laser surgery for refractive accuracy and stability while treating preexisting corneal astigmatism along with surgical aphakia. 4–12…”
mentioning
confidence: 99%